2017
DOI: 10.1097/md.0000000000008992
|View full text |Cite
|
Sign up to set email alerts
|

Left extensive infection in the forearm caused by whitlow infected by mycobacterium tuberculosis

Abstract: Introduction:Whitlow is a common disease in clinic, characterized by pain and swelling of finger. However, few articles had reported on extensive infection in the forearm caused by whitlow infected by mycobacterium tuberculosis (MTB).Patient concerns:A 70-year-old Chinese female complained of fester in back of left hand for 5 days. She had a history of recurrent whitlow for 14 months and pulmonary tuberculosis (TB). She received treatment in another hospital due to whitlow on July 2016. Then she was treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Patel et al [4] presented a rare case of 15-month child with recurrent herpetic whitlow. Wang et al [5] showed a case on recurrent whitlow infected by Mycobacterium tuberculosis . X-ray showed that radius, ulna, and carpal were eroded.…”
Section: Discussionmentioning
confidence: 99%
“…Patel et al [4] presented a rare case of 15-month child with recurrent herpetic whitlow. Wang et al [5] showed a case on recurrent whitlow infected by Mycobacterium tuberculosis . X-ray showed that radius, ulna, and carpal were eroded.…”
Section: Discussionmentioning
confidence: 99%